Alpha lipoic acid antagonizes cytotoxicity of cobalt nanoparticles by inhibiting ferroptosis-like cell death - Yake Liu; Wenfeng Zhu; Dalong Ni; Zihua Zhou; Jin-hua Gu; Weinan Zhang; Huanjian Sun; Fan Liu (Journal of Nanobiotechnology, 2020)
Abstract As a main element in the hard metal industry, cobalt is one of the major components of human metal implants. Cobalt-containing implants, especially joint prostheses used for artificial joint replacement, can be corroded due to the complex physiological environment in vivo, producing a large number of nanoscale cobalt particles (Cobalt Nanoparticles, CoNPs). These CoNPs can be first accumulated around the implant to cause adverse local reactions and then enter into the blood vessels followed by reaching the liver, heart, brain, kidney, and other organs through systematic circulation, which leads to multi-system toxicity symptoms. To ensure the long-term existence of cobalt-containing implants in the body, it is urgently required to find out a safe and effective detoxification drug. Herein, we have demonstrated that CoNPs could induce the ferroptosis-like cell death through the enhancement of intracellular reactive oxygen species (ROS) level, cytoplasmic Fe2+ level, lipid peroxidation, and consumption of reduced glutathione (GSH) as well as inhibition of glutathione peroxidase 4 (GPX4) activity. Importantly, α-lipoic acid (ALA), a natural antioxidant with the capability to scavenge free radicals and chelate toxic metals, was found to efficiently alleviate the adverse effects of CoNPs. The present study illustrates a new mechanism of CoNPs mediated by ferroptosis-like cytotoxicity and discloses an effective method for the detoxification of CoNPs by employing the natural antioxidant of ALA, providing a basis for further in vivo detoxification study.